2019
DOI: 10.1002/jrs.5567
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid formation kinetics of hen egg white lysozyme under heat and acidic conditions revealed by Raman spectroscopy

Abstract: Amyloid fibrillation of proteins is a hallmark of neurodegenerative disease, accompanied by the formation of the organized cross‐β cores. This conformational transformation is considered to be related to the toxicity underlying the pathogenic mechanism. However, the exact conformational transformation kinetics of amyloid fibrillation are not fully understood. Herein, Raman spectroscopy was used to detect the transformation in the molecular structure of hen egg white lysozyme during amyloid formation under heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 81 publications
5
63
0
Order By: Relevance
“…They foresee this statistical technique leading to a widening of the adoption of Raman as a monitoring tool in a field of biofluid analysis. Xing et al [ 58 ] studied the amyloid formation kinetics of hen egg white lysozyme under heat and acidic conditions using Raman. They proposed a four‐stage step‐by‐step transformation mechanism to describe the exact kinetics of lysozyme amyloid fibrillation under heat and acidic conditions, and this provides necessary information for physiologists to artificially control the amyloid formation of neurodegenerative disease patients.…”
Section: Biosciencesmentioning
confidence: 99%
“…They foresee this statistical technique leading to a widening of the adoption of Raman as a monitoring tool in a field of biofluid analysis. Xing et al [ 58 ] studied the amyloid formation kinetics of hen egg white lysozyme under heat and acidic conditions using Raman. They proposed a four‐stage step‐by‐step transformation mechanism to describe the exact kinetics of lysozyme amyloid fibrillation under heat and acidic conditions, and this provides necessary information for physiologists to artificially control the amyloid formation of neurodegenerative disease patients.…”
Section: Biosciencesmentioning
confidence: 99%
“…Lysozymes are a family of globular enzymes in the immune systems of animals. A lysozyme molecule is a single polypeptide of around 130 residues that can partially hydrolyze the peptidoglycans of gram-positive bacterial cell walls [1,2]. Lysozyme is one of the protein types that are associated with the formation of amyloid fibrils under some specific conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Unfolding and refolding of HEWL during amyloidosis could be accelerated under a high temperature and acidic condition. A previous study showed that amyloid fibrils were formed when incubating HEWL under the temperature of 65 °C and pH 2 for 196 hours [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations